An ultrasound based classification of periocular haemangiomas. Issue 11 (15th October 2004) - Bowman, R J C; Nischal, K K; Patel, K; Harper, J I
Abstract : Aims: To propose a classification system for periocular haemangiomas based on ultrasound evaluation. Methods: Retrospective review of ultrasound images from children seen in the authors' unit with periocular haemangiomas. Static ultrasound images from 50 patients with periocular haemangiomas were reviewed as identified from a computerised database. Each haemangioma ultrasound image was classified into three categories: (1) preseptal only; (2) preseptal + extraconal; (3) preseptal + extraconal + intraconal. These were compared with the categories given to each patient at first presentation after dynamic scanning. Results: Classification was possible from the static images in 44 (88%) cases. Of those classified 20 (45%) were preseptal only; 17 (39%) were preseptal + extraconal, and seven (16%) had an additional intraconal component. The classification in all 44 cases was the same as that given at the time of presentation. In the small number of cases which went to surgery or had neuroimaging, the ultrasound classification was confirmed. Conclusions: Ultrasound classification was not difficult to perform and no child needed sedation or general anaesthesia for this exam. Ultrasound anatomical classification is an important first step in determining appropriate treatment of periocular haemangiomas. The authors present what they believe to be the first such classification.